Investigating the disjoint between education and health policy for infant feeding among teenage mothers in South Africa: a case for intersectoral work - Jo Hunter-Adams; Anna Strebel; Joanne Corrigall; Virginia Zweigenthal (BMC, 2022)
Abstract Background Many low-and-middle-income countries, including South Africa, have high rates of teenage pregnancy. Following the World Health Organisation recommendations, South African health policy on infant feeding promotes exclusive breastfeeding until six months of age, with gradual weaning. At the same time, South Africa's education department, in the interest of learners, promotes adolescents' early return to school post-partum. Yet infant feeding at school is currently not perceived as a realistic option. Methods Recognising his this policy tension, we aimed to explore how policies are interpreted and implemented by the health and education sectors through interviews with key informants who produce, interpret and implement these policies. Using an interview guide developed for this study, we conducted in-depth interviews with 24 health policy makers, managers in both sectors, school principals and nursing staff who manage adolescent mothers (aged 16-19) and their babies. Data was analysed using thematic analysis. Results Informants from both sectors expressed discomfort at pregnant learners remaining in school late in pregnancy and were uncertain about policy regarding when to return to school and how long to breast-feed. Educators reported that new mothers typically returned to school within a fortnight after delivery and that breastfeeding was not common. While health professionals highlighted the benefits of extended breastfeeding for infants and mothers, they recognised the potential conflict between the need for the mother to return to school and the recommendation for longer breastfeeding. Additionally, the need for ongoing support of young mothers and their families was highlighted. Conclusions Our findings suggest educators should actively encourage school attendance in a healthy pregnant adolescent until delivery with later return to school, and health providers should focus attention on breastfeeding for the initial 4-6 weeks postpartum, followed by guided support of formula-feeding. We encourage the active engagement of adolescents' mothers and extended families who are often involved in infant feeding and care decisions. Education and health departments must engage to facilitate the interests of both the mother and infant: some exclusive infant feeding together with a supported return to school for the adolescent mother.